Stock discrimination and age validation of Baltic cod (Gadus morhua L.) - Stötera, Sven Sebastian (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
While morphometric or genetic comparisons can assign individual fish to their respective stocks, such methods do not provide information on age or life history patterns, which should ideally be assessed in parallel. Otoliths are calcified tissues in the inner ear of teleost fish and provide characteristics that can be used for both stock discrimination and age estimation. They are chemically inert and have a periodic growth that depends on the environment and physiology of a fish and allows conclusions on its age and life history. However, a reliable assessment requires a variety of methods to account for shortcomings of single features and to cross-validate results, like the periodicity of growth zone formation. The study was conducted on Atlantic cod (Gadus morhua) in the Baltic Sea, where two distinct populations are present and mix. An age discrimination problem in both stocks is recognized, but has never been solved and despite its ecological and economical importance, the timing and magnitude of spatiotemporal overlapping and mixing has only been quantified since 2014, although it has been known for decades. The unacquainted age composition and poor stock identification in the mixing areas is causing a bias in the estimation of stock structure and biological parameter. The overall objective of this study is to determine the feasibility of otolith based methodologies in stock discrimination and age validation that have not been used in Baltic Sea cod before or not as a discriminatory feature prior to this study. Preceding approaches in the discrimination of Baltic Sea cod disclose several shortcomings, where they are not applicable on all stock components or are quite expensive or the regained data are too sparse to make qualified assumptions. I am testing two otolith features for their stock discrimination potential and present a pilot study and the results on an age validation approach for the Western Baltic cod stock. Those methods have never or only partially been used for stock research before. I ...